Revisiting Gender Wage Gap In Egypt: Empirical Evidence Using 2018 ELMPS Data - Zaghloul, Waleed (AUC Knowledge Fountain, 2022)
Recent studies across the different countries suggested that the gender wage gap is not constant in terms of magnitude across the wage distribution adding to the fact that the average wage gap provides limited information on females’ relative position in the labor market. Employing the micro-level data from the Egyptian Labor Force Panel Survey (ELMPS) in 2018, this study investigates the gender wage gap in Egypt across the wage distribution. The quantile regression and the decomposition analysis results in a number of striking results in the Egyptian labor market. The first is that the gender wage gap is not constant across the wage distribution. The second is that the wage gap is more pronounced in the lower quantiles indicating a severe sticky floors effect. The third is that, at the right tail of the wage distribution, a minor glass ceiling effect is found. Finally, female workers are more endowed than their male peers across all the wage distribution yet large wage gaps were evidently indicating an increasing labor market discrimination towards females, especially in the lower segments of the wage distribution.